A new chemical tool for absinthe producers, quantification of α/β-thujone and the bitter components in Artemisia absinthium. (15th December 2016) - Bach, Benoit; Cleroux, Marilyn; Saillen, Mayra; Schönenberger, Patrik; Burgos, Stephane; Ducruet, Julien; Vallat, Armelle
Highlights: HS-SPME-GC–MS method was validated for the thujones analysis in wormwood macerate. UHPLC-HR-MS permitted to obtain quantification of major bitterness compounds. Monitoring the wormwood composition would improve the absinthe production quality. Abstract: The concentrations of α/β-thujone and the bitter components of Artemisia absinthium were quantified from alcoholic wormwood extracts during four phenological stages of their harvest period. A solid-phase micro-extraction method coupled to gas chromatography–mass spectrometry was used to determine the concentration of the two isomeric forms of thujone. In parallel, the combination of ultra-high pressure liquid chromatography and high resolution mass spectrometry allowed to quantify the compounds absinthin, artemisetin and dihydro- epi -deoxyarteannuin B. This present study aimed at helping absinthe producers to determine the best harvesting period.